Modifying modularity: aerobic exercise improves functional connectivity in breast cancer survivors - Page, Lindsey L.; Heller-Wight, Abi; Phipps, Connor J.; Berger, Ann M.; Reed, Elizabeth C.; Warren, David E.; Ehlers, Diane K. (Frontiers in Cognition, 2024)
Aerobic exercise has been shown to improve cancer-associated cognitive decline (CACD) in breast cancer survivors (BCS), and recent findings suggest that one mechanism by which exercise may reduce cognitive decline is through alteration of the brain’s functional organization. Many cognitive abilities and measures of functional brain organization change with age and disease, typically reflected in cognitive decline and reduced differentiation of brain networks, or “modularity.” Although previous research has identified associations between lifestyle interventions, such as exercise, and increased modularity, no studies have examined these relationships in cancer populations. The primary aim of this study was to investigate the preliminary effects of a 12-week aerobic exercise program on changes in brain network modularity in BCS. As a secondary aim, we explored correlations between changes in modularity with moderate-to-vigorous physical activity (MVPA) and cognitive function. Data were exploratory and used for hypothesis generation for a future, larger study. Participants included a subsample of 10 BCS (M age=65.9±9.3 years) from a larger pilot study (N=30 BCS) who were randomized to a 12-week aerobic exercise program (AE) or usual care (UC). The present study collected brain magnetic resonance imaging, Actigraph accelerometry, and cognitive task performance at baseline and 3-month follow-up (i.e., post-intervention; n=4 AE, n=6 UC). Intervention effects on modularity, MVPA, and cognition were quantified as magnitude of change between groups (Cohen’s d). Changes in modularity were further explored via paired t-tests within groups. Associations between changes in modularity, MVPA, and cognitive performance were explored using Spearman’s correlations. The magnitude of changes in modularity between groups were small-to-moderate and favored the AE group (d=0.23 to d=0.67 across thresholds). Paired t-tests revealed a significant increase in modularity in the AE group from baseline to 3-month follow-up (t=3.08, p=.03, d=1.17), but not in the UC group. The correlation between changes in MVPA and changes in modularity were not statistically significant (r=0.36, p=.39), and correlations between modularity and cognitive performance yielded mixed effects by cognitive domain. Our findings suggest that aerobic exercise may influence functional brain network organization and cognition in BCS. These data warrant further investigation in larger exercise trials.